Comparison of Biopsies for Diagnosis of Nasopharyngeal Carcinoma - Cahya, Laila; Muktasim, Lucky; Adji, Iwan Setiawan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This literature review aims to compare accurate biopsy techniques for establishing a diagnosis of nasopharyngeal carcinoma. Methodology: The method used in this research is the systematic literature review method. Results: Several types of biopsy techniques that can be performed to establish a diagnosis of nasopharyngeal carcinoma include nasopharyngeal biopsy and neck biopsy. Nasopharyngeal biopsy is performed if the primary tumor has not spread to other areas. Neck biopsy is performed to determine whether the lump in the neck is a metastasis of nasopharyngeal carcinoma or cancer that originates from the lymph nodes. Applications/Originality/Value: Further research is needed to understand and develop better methods of early detection and diagnosis. With the right approach, the prognosis for patients with nasopharyngeal carcinoma can be significantly improved.